Perlidae (Plecoptera) from Southeastern Santa Catarina State, Southern Brazil - Novaes, Marcos Carneiro [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Magnolia Press, 2014)
Seven species of Perlidae (Plecoptera) from southeastern Santa Catarina State, (Brazil) were studied: Anacroneuria fiorentini De Ribeiro & Froehlich, A. ofaye Froehlich, A. trimacula Jewett, Kempnyia mirim Froehlich, K. neotropica (Jacobson & Bianchi), and K. tenebrosa Klapalek. A new species, A. xokleng is also described.
Keywords: Taxonomy; Streams; Aquatic insects